HIV em gestantes no estado do Amapá: análise epidemiológica no período de 2009 a 2018 - SILVA, Sandro Rogério Mendes da (UNIFAP - Universidade Federal do Amapá, 2022)
HIV in pregnant women is a public health problem, but protective measures during prenatal care can guarantee a safe delivery and quality of life for Mother and Child. The objective of the study was to describe the epidemiological profile of HIV infection in pregnant women in the State of Amapá from 2009 to 2018. 337 notification forms of pregnant women with HIV were analyzed, where the linear regression model showed the existence of a mean increase 2.83 pregnant women with HIV. It was characterized that the majority were residents of the capital Macapá (74.2%), of reproductive age of 20 to 24 years (32.6%), with high school (51%), mixed race (80.1%) and with housewife occupation (79.9%). Related to prenatal, childbirth and puerperium. Regarding laboratory evidence, 46.3% occurred during prenatal care. Most pregnant women received prenatal care (87.5%). Regarding the use of ARV, 79.3% used it during prenatal care and 86.6% used it during delivery. As for the type of delivery, 71.9% had a cesarean delivery. The initiation of ARVRN prophylaxis occurred in the first 24 hours of birth in most pregnant women (92.1%). The increase in the number of cases of pregnant women with HIV is a situation that must be accompanied by health surveillance and primary health care, even more worrying are the cases of late diagnosis, such as those occurring at the time of delivery or after delivery, every pregnant woman needs to know her HIV status during prenatal care.